Metal-Quinoid Carbene Chemistry: From Bonding to C–H Activation Catalysis - Wang, Hai-Xu; Wu, Kai; Che, Chi-Ming (Synlett, 2021)
This account summarizes our recent work on metal-quinoid carbene (QC) chemistry including (a) dirhodium-catalyzed QC C(sp2)–H insertion reactions enabled by a C-centered carbene-transfer reactivity, (b) the isolation, characterization, and dual reactivity of Ru(II) porphyrin QC complexes, and (c) iridium(III) porphyrin-catalyzed QC C(sp3)–H insertion reaction initiated by an O-centered hydrogen-atom transfer reactivity of metal–QC species.1 Introduction2 Catalytic Quinoid Carbene Insertions into C(sp2)–H Bonds Enabled by Carbene-Transfer Reactivity3 Ruthenium(II) Porphyrin Quinoid Carbene Complexes and Dual Reactivity4 Catalytic Quinoid Carbene Insertions into C(sp3)–H Bonds Enabled by Hydrogen-Atom-Transfer Reactivity5 Perspective and Outlook
Keywords: metal carbenes; homogeneous catalysis; C–H functionalization; arylation; quinoid carbenes; hydrogen-atom transfer